OXIDATION OF AN ANTITUMOR DRUG ELLIPTICINE BY PEROXIDASES - Poljaková, Jitka; Forsterová, Kristina; Šulc, Miroslav; Frei, Eva; Stiborová, Marie (Biomedical papers, 2005)
Ellipticine is a potent antineoplastic agent, whose mode of action is considered to be based mainly on DNA intercalation and/or inhibition of topoisomerase II. Since we found that ellipticine also forms the cytochrome P450 (CYP)-mediated covalent DNA adducts, this anticancer drug is considered to function as a pro-drug, whose pharmacological efficiency and/or genotoxic side effects are dependent on its enzymatic activation in target tissues. Here, we demonstrate that ellipticine is also oxidized by peroxidases, which are abundantly expressed in several target tumor tissues. Lactoperoxidase, myeloperoxidase and horseradish peroxidase were used as models. Peroxidases in the presence of hydrogen peroxide oxidize ellipticine to an ellipticine dimer and N2-oxide of ellipticine as the major and minor metabolite, respectively. Inhibition of the peroxidase-mediated ellipticine oxidation by radical scavengers ascorbate, glutathione and NADH suggests a one-electron mechanism of the oxidation. The implication of the oxidation of ellipticine by peroxidases in its mechanism of action is discussed.
Keywords: Ellipticine/Anticancer drug/Peroxidase/Cytochrome P450/Oxidation